Feasibility of using remotely delivered Spring Forest Qigong to reduce neuropathic pain in adults with spinal cord injury: a pilot study - Van de Winckel, Ann; Carpentier, Sydney T.; Deng, Wei; Zhang, Lin; Philippus, Angela; Battaglino, Ricardo; Morse, Leslie R. (Frontiers in Physiology, 2023)
Introduction: About 69% of 299,000 Americans with spinal cord injury (SCI) have debilitating chronic neuropathic pain, which is intractable to treatment. The aim of this study is to determine feasibility, as primary objective, and estimates of efficacy of a remotely delivered Qigong intervention in adults with SCI-related neuropathic pain, as secondary objective. Methods: We recruited adults with SCI-related neuropathic pain, with SCI ≥3 months, with complete or incomplete SCI, and highest neuropathic pain level of >3 on the Numeric Pain Rating Scale (NPRS), using nationwide volunteer sampling. Using a non-randomized controlled trial design, participants practiced Spring Forest Qigong’s “Five Element Qigong Healing Movements” (online video) by combining movement to the best of their ability with kinesthetic imagery, at least 3x/week for 12 weeks. Adherence was automatically tracked through the Spring Forest Qigong website. Outcomes of neuropathic pain intensity (NPRS) were assessed weekly and SCI-related symptoms were assessed at baseline-, 6- and 12-weeks of Qigong practice, and at 6-weeks and 1-year follow-up. Results: We recruited 23 adults with chronic SCI (7/2021-2/2023). Eighteen participants started the study and completed all study components, including the 6-week follow-up. Twelve participants completed the 1-year follow-up assessment. Feasibility was demonstrated through participants' willingness to participate, adherence, and acceptability throughout the 12 weeks. The 18 participants were 60±12 years of age, 15±11 years post-SCI with highest baseline neuropathic pain of 7.94±2.33, which was reduced to 4.17±3.07 after 12 weeks of Qigong practice (Cohen’s d=1.75). This pain relief remained at 6-week and 1-year follow-ups. Participants reported reduced spasm frequency (change score 1.17±1.20, d=0.98) and severity (0.72±1.02, d=0.71), reduced interference of neuropathic pain on mood (3.44±2.53, d=1.36), sleep (3.39±2.40, d=1.41), and daily activities (3.17±2.77, d=1.14), greater ability to perform functional activities (6.68±3.07, d=2.18), and improved mood (2.33±3.31, d=0.70) after Qigong. Discussion: Remote “Five Element Qigong Healing Movements” practice is feasible in adults with SCI-related neuropathic pain, with promising prolonged results of neuropathic pain relief and improvement in SCI-related symptoms after Qigong practice. Trial Registration (this manuscript refers to the quasi-experimental substudy): CREATION: A Clinical Trial of Qigong for Neuropathic Pain Relief in Adults with Spinal Cord Injury, NCT04917107, https://www.clinicaltrials.gov/ct2/show/NCT04917107.